Studies in church history - Parsons, Reuben 1841-1906; Columbia University Libraries (New York F. Pustet, 1896)
v. 1. Centuries I.-VIII -- v. 2. Centuries IX.-XIV -- v. 3. Centuries XV.-XVI -- v. 4. Centuries XVII.-XVIII -- v. 5. Century XIX, pt. I -- v. 6. Century XIX, pt. II.
Vols. 1-2 are 2nd ed. - Includes bibliographical references and index
Keywords: Catholic Church -- History; Church History; Catholic Church